Agile Management in Health Professions Education with Respect to Waterfall Life Cycle - Javed, Rabbia; Fatima, Fozia; Shabnam, Nadia; Qamar, Khadija; Fatima, Sobia; Gul, Ambreen (Pakistan Armed Forces Medical Journal, 2022)
Objective: To determine the practice of waterfall life cycle functions in the health profession department of medical institutes by keeping in view the demographic factors of health professions managers. Study Design: Cross-sectional survey. Place and Duration of Study: Medical Institutes of Rawalpindi and Islamabad Pakistan, from Feb to Jul 2021. Methodology: 46 managers were taken as a sample through a systematic random sampling technique. A self-developed questionnaire was used, and it contained 21 items. Mean and standard deviation were used to measure the practices of waterfall agile management, and t-test and ANOVA were used to test the effect of gender and experiences. Results: Managers were not fully confident about the practices of water fall life cycle functions in their respective organization (Mean=3.08 ± 1.19). Gender has no significant effect on required analysis (p=0.861); design stage (p=0.625); test (p=0.222); deployment (p=0.718) and development (p=0.432) while monitoring and evaluation had significant effect (p=0.042). Similarly, managers’ experience has significant effect on required analysis (p=0.013); test (p=0.001); deployment (p≤0.001) and development (p=0.002) while it has no significant effect on design stage (p=0.062) and monitoring and evaluation (p=0.060) in medical institutes. Conclusion: Health profession managers were neutral about the practices of the waterfall life cycle of agile management in their respective medical institutes.